If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + -6Y = 2 Solving 2X + -6Y = 2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6Y' to each side of the equation. 2X + -6Y + 6Y = 2 + 6Y Combine like terms: -6Y + 6Y = 0 2X + 0 = 2 + 6Y 2X = 2 + 6Y Divide each side by '2'. X = 1 + 3Y Simplifying X = 1 + 3Y
| 9y=x | | 0.5x^4+1=1.25x^3-1 | | 9x+25=4x | | -6x+5=2-3-5x+x | | x^4+x-2=0 | | 4m-5=m-5 | | 7+7x=6x-9 | | 11x+33=5x-129 | | x-(0.03x)=29 | | 6t^2-5t-4=0 | | -14=x+12/-6 | | 3x+8=89-6 | | 2/3w=8 | | 3(x+7)2+17=25 | | 1/2x=3 | | p=25 | | -3/4(12x-8)=-18 | | 20-4x=5x-35 | | a^2+2a+8=0 | | x-6=42 | | 4x+y=-20 | | 2p-1=3y+11 | | 29-H=207 | | 9x-4x+32=6x-21 | | 33=0+3y | | 3y-2y=8x | | y=3/5+9 | | y=2.5x-2 | | 21/p+1=8 | | a^2-2a+8=0 | | 15+(-4x-18)=9 | | 5n-7=3n-9 |